“PROYECTO DE FACTIBILIDAD PARA LA IMPLEMENTACIÓN DE UNA PASTELERÍA EN EL CANTÓN CENTINELA DEL CÓNDOR, PROVINCIA DE ZAMORA CHINCHIPE” - Álvarez Jiménez, Angela Nataly (2024)
This research work was carried out in the Canton Centinela del Cóndor, in the province of Zamora Chinchipe, with the objective of determining the feasibility of implementing a bakery. Among the objectives, it was proposed to carry out a market study to know the current demand, supply and unsatisfied demand, design the technical and administrative structure, which are needed to start the project, in addition, determine the macro and micro location, and finally carry out a financial and economic study to establish the investment of the project and to determine the feasibility or not of the project under study. Regarding the methods used in the research, the inductive method was taken into account to interpret the information collected; The descriptive method provides each of the details of the creation of the bakery; and through the analytical method, the data collected are detailed. In addition, observation techniques, interviews and surveys were used. Finally, the evaluation of the project was carried out to establish the convenience of the project and its execution for which the following indicators were analyzed as the Financial Evaluation, the present project has the following indicators: Net Present Value of $ 138,943; Internal Rate of Return of 68.76%; Benefit Cost Ratio is $2.39 for every dollar invested the company earns 1.39 cents of a dollar; Capital Recovery Period is less than 1 year, 5 months and 4 days; Sensitivity Analysis indicates that the project supports an increase in costs of 2.54% giving a total of 44.57% and the sensitivity analysis in the decrease in income of 2.18% giving a total of 44.12%, for which the project is feasible, whose conclusions and recommendations so determine, attaching the consulted bibliography with their respective annexes.